A UV-cured epoxy resin adhesive and a preparation method thereof

CN122941333APending Publication Date: 2026-10-20EUNOW ELECTRONICS TECH CO LTD SUZHOU
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611214245.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-11
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0003]然而,现有的双重固化胶黏剂仍存在一些问题

Benefits of technology

1、在紫外光照下,阳离子光引发剂与增感剂配合实现前端引发,促使表层脂环族环氧树脂快速发生阳离子开环聚合,形成交联网络并释放热量;该热量激发自由基引发剂分解产生自由基,自由基进一步向未受光照的深层区域传递能量,激活深层阳离子光引发剂,使其在无光条件下持续引发阳离子聚合反应,从而实现能量逐级传递与深层固化;同时,脂环族环氧树脂构建的刚性交联网络与柔性桥接剂中的聚醚多元醇参与反应,形成刚柔并济的杂化结构,提升了胶黏剂的耐热性和耐水性,并降低了体积收缩率;气相白炭黑与硅微粉的加入改善了体系的储存稳定性,使胶黏剂兼具低收缩率与适用于LIPO制程的固化性能。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

This application relates to a UV-curable epoxy resin adhesive and its preparation method, belonging to the field of adhesives. The raw materials for preparation include the following components in parts by weight: 35-45 parts of alicyclic epoxy resin, 15-25 parts of toughening filler, 1-3 parts of fumed silica, 10-20 parts of flexible bridging agent, 15-25 parts of silica powder, 0.8-1.2 parts of cationic photoinitiator, 0.8-1.2 parts of free radical initiator, and 0.8-1.2 parts of sensitizer; the flexible bridging agent includes polyether polyol. The preparation method includes the following steps: mixing and stirring the above components sequentially to complete premixing, obtaining an adhesive solution, and degassing the adhesive solution under vacuum to obtain the UV-curable epoxy resin adhesive. This application has the effect of improving the heat resistance, water resistance, storage stability, and curing depth of the adhesive, and can reduce its volume shrinkage rate, making the adhesive suitable for bonding various complex substrates.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of adhesives, and in particular to a UV-curable epoxy resin adhesive and its preparation method. Background Technology

[0002] With the rapid development of technology, adhesives are increasingly widely used in electronics, communications, aerospace, and many other fields, bringing great convenience and significant value to product manufacturing, assembly, and performance assurance in these areas. In electronic products, adhesives are used to fix and seal components, ensuring the stability and reliability of electronic devices. In the communications field, they ensure the stable connection of signal transmission components and reduce signal interference. In the aerospace field, there are also application scenarios with extremely high requirements for material performance, such as the bonding of aircraft components. Traditional single-curing adhesives are no longer suitable for complex and ever-changing usage environments. Therefore, dual-curing mechanisms have gradually become a hot research direction, especially UV-thermal dual-curing methods, which combine the advantages of UV curing and thermal curing and have received widespread attention.

[0003] However, existing dual-curing adhesives still have some problems. For example, some products perform poorly in terms of heat and water resistance, have high curing temperatures, and limit their application range. Furthermore, some adhesives experience volume shrinkage during curing, affecting the dimensional accuracy and bond strength of the product. Traditional UV-curing adhesives cannot be used for opaque materials, limiting their application in certain fields. Therefore, developing a dual-curing adhesive with excellent heat and water resistance, and long-term shelf life at room temperature, has become a current research focus. Summary of the Invention

[0004] To address the aforementioned issues, this application provides a UV-curable epoxy resin adhesive and its preparation method.

[0005] This application provides a UV-curable epoxy resin adhesive and its preparation method, which adopts the following technical solution: In a first aspect, this application provides a UV-curable epoxy resin adhesive, which adopts the following technical solution: A UV-curable epoxy resin adhesive, the raw materials for which are prepared include the following components in parts by weight: 35-45 parts of alicyclic epoxy resin 15-25 parts toughening filler 1-3 parts of fumed silica 10-20 parts of flexible bridging agent 15-25 parts of silicon micro powder 0.8-1.2 parts of cationic photoinitiator 0.8-1.2 parts of free radical initiator Sensitizer 0.8-1.2 parts; The flexible bridging agent includes polyether polyols.

[0006] Under ultraviolet light, the cationic photoinitiator and sensitizer work together to initiate the process at the front end, causing the surface alicyclic epoxy resin to undergo rapid cationic ring-opening polymerization, forming a cross-linked network and releasing heat. This heat excites the free radical initiator to decompose and generate free radicals, which further transfer energy to the unexposed deep regions, activating the deep cationic photoinitiator and enabling it to continue initiating the cationic polymerization reaction under light-free conditions, thereby achieving stepwise energy transfer and deep curing. At the same time, the rigid cross-linked network constructed by the alicyclic epoxy resin and the polyether polyol in the flexible bridging agent participate in the reaction to form a hybrid structure that combines rigidity and flexibility, improving the heat resistance and water resistance of the adhesive and reducing the volume shrinkage rate. The addition of fumed silica and silica powder improves the storage stability of the system, giving the adhesive both low shrinkage and curing performance suitable for LIPO processes.

[0007] Preferably, the toughening filler comprises methyl methacrylate-butadiene-styrene copolymer.

[0008] Methyl methacrylate-butadiene-styrene copolymer, used as a toughening filler, forms a micro-phase separation region in its core-shell structure after adhesive curing. This region absorbs impact energy through the rubber phase and terminates crack propagation, improving the adhesive's thermal shock resistance and water resistance while maintaining the overall stability of the crosslinked network. During UV-induced cationic front-end polymerization, this toughening filler does not interfere with the energy transfer between the photoinitiator and sensitizer. Furthermore, its shell layer exhibits good compatibility with the epoxy resin matrix, ensuring a smooth surface curing and exothermic process. This heat is successfully transferred to the deeper layers to drive the free radical initiator reaction, achieving a high curing depth. The copolymer is uniformly dispersed in the system as solid particles, does not participate in the curing reaction, and synergistically maintains the adhesive's storage stability with fillers such as fumed silica and silica fume. Its addition does not introduce additional shrinkage stress, helping to reduce volume shrinkage.

[0009] Preferably, the cationic photoinitiator comprises an arylthionium salt derivative.

[0010] Aryl thioonium salt derivatives, acting as cationic photoinitiators, decompose upon absorbing light energy under ultraviolet light to produce a superacid, initiating the ring-opening polymerization reaction of alicyclic epoxy resins to form a cross-linked network, thus improving the heat and water resistance of the adhesive. When used in conjunction with sensitizers, they achieve rapid initiation at the front end under light conditions, promoting the rapid curing of the surface resin and releasing heat. This heat is transferred to the deeper layers, activating free radical initiators and causing polymerization reactions in the deeper regions, thereby increasing the curing depth. This photoinitiator exhibits good chemical stability under yellow light conditions, good compatibility with the components in the system, and is not prone to decomposition or side reactions during storage. It works synergistically with fillers such as fumed silica and silica fume to maintain the storage stability of the adhesive. The cationic ring-opening polymerization reaction initiated by it has minimal volume shrinkage, which helps to reduce the volume shrinkage rate of the adhesive.

[0011] Preferably, the free radical initiator comprises cumene peroxide.

[0012] As a free radical initiator, cumene peroxide utilizes the heat released from the ring-opening reaction of the surface alicyclic epoxy resin to reach its decomposition temperature during the cationic front-end polymerization initiated by ultraviolet light, generating free radicals to initiate polymerization reactions in deeper regions, thus enhancing the curing depth of the adhesive. Its decomposition products participate in the formation of an interpenetrating network structure, synergistically working with the cationic curing network to improve the heat and water resistance of the adhesive. This initiator exhibits good chemical stability under room temperature storage conditions, is not easily decomposed in yellow light operating environments, and has good compatibility with all components in the system. Combined with fillers such as fumed silica and silica fume, it maintains the storage stability of the adhesive. The free radical polymerization reaction initiated by it, together with the cationic ring-opening polymerization, completes the crosslinking process, controlling volume shrinkage and helping to maintain a low volume shrinkage rate.

[0013] Preferably, the sensitizer comprises 5,7-diiodo-3-butoxy-6-fluorescein.

[0014] 5,7-Diiodo-3-butoxy-6-fluorescein, acting as a sensitizer, absorbs light energy under ultraviolet light and transfers the excitation energy to the cationic photoinitiator via an energy transfer mechanism, enhancing photoinitiation efficiency. This enables the alicyclic epoxy resin to rapidly undergo ring-opening polymerization in the illuminated region, forming a surface cross-linked network and releasing heat. This heat transfer to deeper layers drives the decomposition of free radical initiators, causing polymerization reactions in deeper regions and increasing the curing depth of the adhesive. Its participation in the photosensitization process promotes the uniform formation of the cross-linked network, reduces the residue of unreacted groups, and improves the heat resistance and water resistance of the adhesive. This sensitizer exhibits good chemical stability under yellow light conditions, good compatibility with other components in the system, and is not prone to precipitation or side reactions during storage. It works synergistically with fillers such as fumed silica and silica fume to maintain the storage stability of the adhesive. Its energy transfer promotes cationic ring-opening polymerization, ensuring a smooth curing process and helping to maintain a low volume shrinkage rate.

[0015] Preferably, the alicyclic epoxy resin comprises 3',4'-epoxycyclohexylmethyl-3,4-epoxycyclohexane carboxylate.

[0016] 3',4'-Epoxycyclohexylmethyl-3,4-epoxycyclohexane carboxylate participates in cationic photocuring reactions through its unique alicyclic structure. The resulting crosslinked network has a high rigidity segment density, improving the heat resistance and water resistance of the adhesive. Simultaneously, its ring-opening polymerization process exhibits minimal volume shrinkage, contributing to a lower volume shrinkage rate. Under ultraviolet light, this resin, in conjunction with cationic photoinitiators and sensitizers, undergoes a pre-polymerization reaction. The released heat further drives the free radical initiator to initiate curing at a deeper level, enhancing the curing depth. Its low viscosity and good reactivity contribute to the uniform dispersion of components in the system. Synergistically, it works with fillers such as fumed silica and silica fume to improve the storage stability of the adhesive.

[0017] Preferably, the alicyclic epoxy resin further includes poly[(2-epoxyethylene)-1,2-cyclohexanediol]2-ethyl-2-(hydroxymethyl)-1,3-propanediol ether.

[0018] By introducing poly[(2-epoxyethylene)-1,2-cyclohexanediol]2-ethyl-2-(hydroxymethyl)-1,3-propanediol ether as a component of alicyclic epoxy resin, its multifunctional molecular structure is utilized to construct a crosslinking network with the original 3',4'-epoxycyclohexylmethyl-3,4-epoxycyclohexane carboxylate. This network reacts with the polyether polyol in the flexible bridging agent to form a hybrid network structure that combines rigidity and flexibility. This improves the heat resistance and water resistance of the adhesive and reduces the volume shrinkage rate.

[0019] Preferably, the mass ratio of the 3',4'-epoxycyclohexylmethyl-3,4-epoxycyclohexane carboxylate to poly[(2-epoxyethylene)-1,2-cyclohexanediol]2-ethyl-2-(hydroxymethyl)-1,3-propanediol ether is 1:(0.2-0.3).

[0020] By controlling the ratio of the two alicyclic epoxy resins within the aforementioned range, the multifunctional poly[(2-epoxyethylene)-1,2-cyclohexanediol]2-ethyl-2-(hydroxymethyl)-1,3-propanediol ether and the bifunctional 3',4'-epoxycyclohexylmethyl-3,4-epoxycyclohexane carboxylate achieve a synergistic effect in the system. The two react with the polyether polyol in the flexible bridging agent to form a hybrid network structure that combines rigidity and flexibility. This ensures sufficient crosslinking density while reducing internal stress generated during curing, improving the heat resistance and water resistance of the adhesive, and reducing the volume shrinkage rate.

[0021] Secondly, this application provides a method for preparing a UV-curable epoxy resin adhesive, using the following technical solution: A method for preparing a UV-curable epoxy resin adhesive includes the following steps: After stirring and dispersing alicyclic epoxy resin, toughening filler and flexible bridging agent, fumed silica and silica powder are added, and after stirring, cationic photoinitiator, sensitizer and free radical initiator are added. After stirring to complete the premixing, a glue solution is obtained. The glue solution is degassed under vacuum to obtain UV-curable epoxy resin adhesive.

[0022] First, the alicyclic epoxy resin, toughening filler, and flexible bridging agent are stirred and dispersed to ensure thorough and uniform mixing of the polymer components and toughening phase, forming a stable premixed system. This provides a foundation for the uniform construction of the subsequent crosslinking network and improves the heat resistance and water resistance of the adhesive. Then, fumed silica and silica powder are added and stirred to ensure uniform dispersion of the inorganic filler in the resin matrix. The thixotropic properties of fumed silica enhance the storage stability of the system, while the rigid particles of silica powder help reduce the volume shrinkage rate during curing. Finally, cationic photoinitiator, sensitizer, and free radical initiator are added to complete the premixing. Under yellow light conditions, premature decomposition of the photoinitiator is avoided, ensuring that the cationic photoinitiator and sensitizer work together to initiate the process under ultraviolet light, promoting rapid surface curing and releasing heat. This heat is transferred to deeper layers, driving the decomposition of the free radical initiator to initiate the polymerization reaction, achieving a high curing depth. Vacuum degassing of the adhesive removes air bubbles, resulting in a dense and uniform cured adhesive layer, further improving heat resistance and water resistance, and effectively controlling volume shrinkage.

[0023] In summary, this application includes at least one of the following beneficial technical effects: 1. Under ultraviolet light, the cationic photoinitiator and sensitizer work together to initiate the process at the front end, causing the surface alicyclic epoxy resin to undergo rapid cationic ring-opening polymerization, forming a cross-linked network and releasing heat. This heat excites the free radical initiator to decompose and generate free radicals, which further transfer energy to the unexposed deep regions, activating the deep cationic photoinitiator and enabling it to continue initiating the cationic polymerization reaction under light-free conditions, thereby achieving stepwise energy transfer and deep curing. At the same time, the rigid cross-linked network constructed by the alicyclic epoxy resin and the polyether polyol in the flexible bridging agent participate in the reaction to form a hybrid structure that combines rigidity and flexibility, improving the heat resistance and water resistance of the adhesive and reducing the volume shrinkage rate. The addition of fumed silica and silica powder improves the storage stability of the system, giving the adhesive both low shrinkage and curing performance suitable for LIPO processes.

[0024] 2. By introducing poly[(2-epoxyethylene)-1,2-cyclohexanediol]2-ethyl-2-(hydroxymethyl)-1,3-propanediol ether as a component of alicyclic epoxy resin, its multifunctional molecular structure is utilized to construct a crosslinking network together with the original 3',4'-epoxycyclohexylmethyl-3,4-epoxycyclohexane carboxylate. This network reacts with the polyether polyol in the flexible bridging agent to form a hybrid network structure that combines rigidity and flexibility, thereby improving the heat resistance and water resistance of the adhesive and reducing the volume shrinkage rate. Detailed Implementation

[0025] This application discloses a UV-curable epoxy resin adhesive and its preparation method. Unless otherwise specified, all raw materials used in this application are commercially available. The following detailed description, in conjunction with embodiments, further illustrates this application: Raw material specifications: Daicel Celloxide 2021p (Japan) was purchased from Shanghai Wandao Chemical Co., Ltd.; DuPont Paraloid™ BPM-520 was purchased from Dongguan Donglin Polymer Materials Co., Ltd.; Degussa R202 was purchased from Shanghai Jiuqing International Trade Co., Ltd.; polyether polyol was purchased from Hubei Xinghengye Technology Co., Ltd.; silica powder was purchased from Hebei Wensheng New Material Technology Co., Ltd.; cationic photoinitiator R-Gen-262 (CAS No.: 100011-37-8); free radical initiator TRIGONOX® K-80 (CAS No.: 80-15-9); sensitizer H-Nu 470 (CAS No.: 161728-47-8), 1,4-butanediol diglycidyl ether (CAS No.: 2425-79-8), γ-butyrolactone (CAS No.: 96-48-0), trimethylolpropane monoallyl ether (CAS No.: 682-11-1), di-n-butyltin oxide (CAS No.: 818-08-6), poly[(2-epoxyethylene)-1,2-cyclohexanediol]2-ethyl-2-(hydroxymethyl)-1,3-propanediol ether (CAS No.: 244772-00-7), purchased from Beijing Ansimosen Technology Co., Ltd. Example 1

[0026] Preparation of UV-curable epoxy resin adhesives Weigh out 35 parts of alicyclic epoxy resin, 15 parts of toughening filler, 1 part of fumed silica, 10 parts of flexible bridging agent, 15 parts of silica powder, 0.8 parts of cationic photoinitiator, 0.8 parts of free radical initiator, and 0.8 parts of sensitizer. The alicyclic epoxy resin is 3',4'-epoxycyclohexylmethyl-3,4-epoxycyclohexane carboxylate, model: Daicel Celloxide 2021p (Japan); the toughening filler is methyl methacrylate-butadiene-styrene copolymer, model: DuPont PARALOID™ BPM-520; the fumed silica is model: Degussa R202; the flexible bridging agent is polyether polyol 5000; the silica powder particle size is 0.6 μm; the cationic photoinitiator is aryl thioonium salt derivative, model: R-Gen-262; and the free radical initiator is cumene peroxide, model: TRIGONOX. K-80 uses 5,7-diiodo-3-butoxy-6-fluorescein as a sensitizer, model number H-Nu 470.

[0027] Under yellow light conditions, alicyclic epoxy resin, toughening filler, and flexible bridging agent are added sequentially to a high-speed dispersion tank. After stirring and dispersing at 1500 rpm for 15 min, fumed silica and silica powder are added, and the mixture is stirred at 1500 rpm for 10 min. Then, cationic photoinitiator, sensitizer, and free radical initiator are added, and the mixture is stirred at 1500 rpm for 2 min to complete the premixing, resulting in a glue solution. The glue solution is transferred to a vacuum degassing autoclave and degassed under vacuum at 80℃ for 2 h to obtain the UV-cured epoxy resin adhesive. Example 2

[0028] Weigh out 45 parts of alicyclic epoxy resin, 25 parts of toughening filler, 3 parts of fumed silica, 20 parts of flexible bridging agent, 25 parts of silica powder, 1.2 parts of cationic photoinitiator, 1.2 parts of free radical initiator, and 1.2 parts of sensitizer. The alicyclic epoxy resin is 3',4'-epoxycyclohexylmethyl-3,4-epoxycyclohexane carboxylate, model: Daicel Celloxide 2021p (Japan); the toughening filler is methyl methacrylate-butadiene-styrene copolymer, model: DuPont PARALOID™ BPM-520; the fumed silica is model: Degussa R202; the flexible bridging agent is polyether polyol 5000; the silica powder particle size is 0.6 μm; the cationic photoinitiator is aryl thioonium salt derivative, model: R-Gen-262; and the free radical initiator is cumene peroxide, model: TRIGONOX. K-80 uses 5,7-diiodo-3-butoxy-6-fluorescein as a sensitizer, model number H-Nu 470.

[0029] Under yellow light conditions, alicyclic epoxy resin, toughening filler, and flexible bridging agent are added sequentially to a high-speed dispersion tank. After stirring and dispersing at 1500 rpm for 15 min, fumed silica and silica powder are added, and the mixture is stirred at 1500 rpm for 10 min. Then, cationic photoinitiator, sensitizer, and free radical initiator are added, and the mixture is stirred at 1500 rpm for 2 min to complete the premixing, resulting in a glue solution. The glue solution is transferred to a vacuum degassing autoclave and degassed under vacuum at 80℃ for 2 h to obtain the UV-cured epoxy resin adhesive. Example 3

[0030] Weigh out 40 parts of alicyclic epoxy resin, 20 parts of toughening filler, 2 parts of fumed silica, 15 parts of flexible bridging agent, 20 parts of silica powder, 1 part of cationic photoinitiator, 1 part of free radical initiator, and 1 part of sensitizer. The alicyclic epoxy resin is 3',4'-epoxycyclohexylmethyl-3,4-epoxycyclohexane carboxylate, model: Daicel Celloxide 2021p (Japan); the toughening filler is methyl methacrylate-butadiene-styrene copolymer, model: DuPont PARALOID™ BPM-520; the fumed silica is model: Degussa R202; the flexible bridging agent is polyether polyol 5000; the silica powder particle size is 0.6 μm; the cationic photoinitiator is aryl thioonium salt derivative, model: R-Gen-262; and the free radical initiator is cumene peroxide, model: TRIGONOX. K-80 uses 5,7-diiodo-3-butoxy-6-fluorescein as a sensitizer, model number H-Nu 470.

[0031] Under yellow light conditions, alicyclic epoxy resin, toughening filler, and flexible bridging agent are added sequentially to a high-speed dispersion tank. After stirring and dispersing at 1500 rpm for 15 min, fumed silica and silica powder are added, and the mixture is stirred at 1500 rpm for 10 min. Then, cationic photoinitiator, sensitizer, and free radical initiator are added, and the mixture is stirred at 1500 rpm for 2 min to complete the premixing, resulting in a glue solution. The glue solution is transferred to a vacuum degassing autoclave and degassed under vacuum at 80℃ for 2 h to obtain the UV-cured epoxy resin adhesive. Example 4

[0032] In Example 4, the alicyclic epoxy resin further includes poly[(2-epoxyethylene)-1,2-cyclohexanediol]2-ethyl-2-(hydroxymethyl)-1,3-propanediol ether, 3',4'-epoxycyclohexylmethyl-3,4-epoxycyclohexane carboxylate, and poly[(2-epoxyethylene)-1,2-cyclohexanediol]2-ethyl-2-(hydroxymethyl)-1,3-propanediol ether in a mass ratio of 1:0.2.

[0033] Preparation of UV-curable epoxy resin adhesives Weigh out 40 parts of alicyclic epoxy resin, 20 parts of toughening filler, 2 parts of fumed silica, 15 parts of flexible bridging agent, 20 parts of silica powder, 1 part of cationic photoinitiator, 1 part of free radical initiator, and 1 part of sensitizer. The alicyclic epoxy resin is composed of 3',4'-epoxycyclohexylmethyl-3,4-epoxycyclohexane carboxylate and poly[(2-epoxyethylene)-1,2-cyclohexanediol]2-ethyl-2-(hydroxymethyl)-1,3-propanediol ether in a mass ratio of 1:0.2. The 3',4'-epoxycyclohexylmethyl-3,4-epoxycyclohexane carboxylate is of the Japanese brand Celloxide 2021p. The toughening filler is methyl methacrylate-butadiene-styrene copolymer, of the DuPont PARALOID™ brand. BPM-520, fumed silica model is Degussa R202, flexible bridging agent is polyether polyol 5000, silica powder particle size is 0.6μm, cationic photoinitiator is aryl thioonium salt derivative model is R-Gen-262, free radical initiator is cumene peroxide model is TRIGONOX K-80, sensitizer is 5,7-diiodo-3-butoxy-6-fluorescein model is H-Nu 470.

[0034] Under yellow light conditions, alicyclic epoxy resin, toughening filler, and flexible bridging agent are added sequentially to a high-speed dispersion tank. After stirring and dispersing at 1500 rpm for 15 min, fumed silica and silica powder are added, and the mixture is stirred at 1500 rpm for 10 min. Then, cationic photoinitiator, sensitizer, and free radical initiator are added, and the mixture is stirred at 1500 rpm for 2 min to complete the premixing, resulting in a glue solution. The glue solution is transferred to a vacuum degassing autoclave and degassed under vacuum at 80℃ for 2 h to obtain the UV-cured epoxy resin adhesive. Example 5

[0035] In Example 5, the alicyclic epoxy resin further includes poly[(2-epoxyethylene)-1,2-cyclohexanediol]2-ethyl-2-(hydroxymethyl)-1,3-propanediol ether, 3',4'-epoxycyclohexylmethyl-3,4-epoxycyclohexane carboxylate, and poly[(2-epoxyethylene)-1,2-cyclohexanediol]2-ethyl-2-(hydroxymethyl)-1,3-propanediol ether in a mass ratio of 1:0.3.

[0036] Preparation of UV-curable epoxy resin adhesives Weigh out 40 parts of alicyclic epoxy resin, 20 parts of toughening filler, 2 parts of fumed silica, 15 parts of flexible bridging agent, 20 parts of silica powder, 1 part of cationic photoinitiator, 1 part of free radical initiator, and 1 part of sensitizer. The alicyclic epoxy resin is composed of 3',4'-epoxycyclohexylmethyl-3,4-epoxycyclohexane carboxylate and poly[(2-epoxyethylene)-1,2-cyclohexanediol]2-ethyl-2-(hydroxymethyl)-1,3-propanediol ether in a mass ratio of 1:0.3. The 3',4'-epoxycyclohexylmethyl-3,4-epoxycyclohexane carboxylate is model number Celloxide 2021p from Daicel Japan. The toughening filler is methyl methacrylate-butadiene-styrene copolymer, model number DuPont PARALOID™. BPM-520, fumed silica model is Degussa R202, flexible bridging agent is polyether polyol 5000, silica powder particle size is 0.6μm, cationic photoinitiator is aryl thioonium salt derivative model is R-Gen-262, free radical initiator is cumene peroxide model is TRIGONOX K-80, sensitizer is 5,7-diiodo-3-butoxy-6-fluorescein model is H-Nu 470.

[0037] Under yellow light conditions, alicyclic epoxy resin, toughening filler, and flexible bridging agent are added sequentially to a high-speed dispersion tank. After stirring and dispersing at 1500 rpm for 15 min, fumed silica and silica powder are added, and the mixture is stirred at 1500 rpm for 10 min. Then, cationic photoinitiator, sensitizer, and free radical initiator are added, and the mixture is stirred at 1500 rpm for 2 min to complete the premixing, resulting in a glue solution. The glue solution is transferred to a vacuum degassing autoclave and degassed under vacuum at 80℃ for 2 h to obtain the UV-cured epoxy resin adhesive. Example 6

[0038] In Example 6, the alicyclic epoxy resin further includes poly[(2-epoxyethylene)-1,2-cyclohexanediol]2-ethyl-2-(hydroxymethyl)-1,3-propanediol ether, 3',4'-epoxycyclohexylmethyl-3,4-epoxycyclohexane carboxylate, and poly[(2-epoxyethylene)-1,2-cyclohexanediol]2-ethyl-2-(hydroxymethyl)-1,3-propanediol ether in a mass ratio of 1:0.25.

[0039] Preparation of UV-curable epoxy resin adhesives Weigh out 40 parts of alicyclic epoxy resin, 20 parts of toughening filler, 2 parts of fumed silica, 15 parts of flexible bridging agent, 20 parts of silica powder, 1 part of cationic photoinitiator, 1 part of free radical initiator, and 1 part of sensitizer. The alicyclic epoxy resin is composed of 3',4'-epoxycyclohexylmethyl-3,4-epoxycyclohexane carboxylate and poly[(2-epoxyethylene)-1,2-cyclohexanediol]2-ethyl-2-(hydroxymethyl)-1,3-propanediol ether in a mass ratio of 1:0.25. The 3',4'-epoxycyclohexylmethyl-3,4-epoxycyclohexane carboxylate is Celloxide 2021p from Daicel Japan. The toughening filler is methyl methacrylate-butadiene-styrene copolymer, model DuPont PARALOID™. BPM-520, fumed silica model is Degussa R202, flexible bridging agent is polyether polyol 5000, silica powder particle size is 0.6μm, cationic photoinitiator is aryl thioonium salt derivative model is R-Gen-262, free radical initiator is cumene peroxide model is TRIGONOX K-80, sensitizer is 5,7-diiodo-3-butoxy-6-fluorescein model is H-Nu 470.

[0040] Under yellow light conditions, alicyclic epoxy resin, toughening filler, and flexible bridging agent are added sequentially to a high-speed dispersion tank. After stirring and dispersing at 1500 rpm for 15 min, fumed silica and silica powder are added, and the mixture is stirred at 1500 rpm for 10 min. Then, cationic photoinitiator, sensitizer, and free radical initiator are added, and the mixture is stirred at 1500 rpm for 2 min to complete the premixing, resulting in a glue solution. The glue solution is transferred to a vacuum degassing autoclave and degassed under vacuum at 80℃ for 2 h to obtain the UV-cured epoxy resin adhesive. Example 7

[0041] Example 7 is based on Example 6. The only difference between Example 7 and Example 6 is that in Example 7, the mass ratio of 3',4'-epoxycyclohexylmethyl-3,4-epoxycyclohexane carboxylate and poly[(2-epoxyethylene)-1,2-cyclohexanediol]2-ethyl-2-(hydroxymethyl)-1,3-propanediol ether in the alicyclic epoxy resin is 1:0.1. Example 8

[0042] Example 8 is based on Example 6. The only difference between Example 8 and Example 6 is that in Example 8, the mass ratio of 3',4'-epoxycyclohexylmethyl-3,4-epoxycyclohexane carboxylate and poly[(2-epoxyethylene)-1,2-cyclohexanediol]2-ethyl-2-(hydroxymethyl)-1,3-propanediol ether in the alicyclic epoxy resin is 1:0.4. Example 9

[0043] Example 9 is based on Example 6. The only difference between Example 9 and Example 6 is that in Example 9, the alicyclic epoxy resin is only mixed with poly[(2-epoxyethylene)-1,2-cyclohexanediol]2-ethyl-2-(hydroxymethyl)-1,3-propanediol ether.

[0044] Comparative Example 1 Comparative Example 1 is based on Example 1. The only difference between Comparative Example 1 and Example 1 is that no free radical initiator is added in Comparative Example 1.

[0045] Weigh out 40 parts of alicyclic epoxy resin, 20 parts of toughening filler, 2 parts of fumed silica, 15 parts of flexible bridging agent, 20 parts of silica powder, 1 part of cationic photoinitiator, and 1 part of sensitizer. The alicyclic epoxy resin is 3',4'-epoxycyclohexylmethyl-3,4-epoxycyclohexane carboxylate, model number: Daicel Celloxide 2021p; the toughening filler is methyl methacrylate-butadiene-styrene copolymer, model number: DuPont PARALOID™ BPM-520; the fumed silica is model number: Degussa R202; the flexible bridging agent is polyether polyol 5000; the silica powder has a particle size of 0.6 μm; the cationic photoinitiator is aryl thioonium salt derivative, model number: R-Gen-262; and the sensitizer is 5,7-diiodo-3-butoxy-6-fluorescein, model number: H-Nu 470.

[0046] Under yellow light conditions, alicyclic epoxy resin, toughening filler, and flexible bridging agent are added sequentially to a high-speed dispersion tank. After stirring and dispersing at 1500 rpm for 15 min, fumed silica and silica powder are added, and the mixture is stirred at 1500 rpm for 10 min. Then, cationic photoinitiator and sensitizer are added, and the mixture is stirred at 1500 rpm for 2 min to complete the premixing and obtain the adhesive solution. The adhesive solution is transferred to a vacuum degassing autoclave and degassed under vacuum at 80℃ for 2 h to obtain the UV-cured epoxy resin adhesive.

[0047] Comparative Example 2 Comparative Example 2 is based on Example 1. The only difference between Comparative Example 2 and Example 1 is that no flexible bridging agent is added in Comparative Example 2.

[0048] Weigh out 40 parts of alicyclic epoxy resin, 20 parts of toughening filler, 2 parts of fumed silica, 20 parts of silica powder, 1 part of cationic photoinitiator, 1 part of free radical initiator, and 1 part of sensitizer. The alicyclic epoxy resin is 3',4'-epoxycyclohexylmethyl-3,4-epoxycyclohexane carboxylate, model: Celloxide 2021p (Japan); the toughening filler is methyl methacrylate-butadiene-styrene copolymer, model: DuPont PARALOID™ BPM-520; the fumed silica is model: Degussa R202; the silica powder has a particle size of 0.6 μm; the cationic photoinitiator is an aryl thioonium salt derivative, model: R-Gen-262; the free radical initiator is cumene peroxide, model: TRIGONOX K-80; and the sensitizer is 5,7-diiodo-3-butoxy-6-fluorescein, model: H-Nu 470.

[0049] Under yellow light conditions, alicyclic epoxy resin and toughening filler were added sequentially to a high-speed dispersion tank and stirred and dispersed at 1500 rpm for 15 min. Then, fumed silica and silica powder were added and stirred at 1500 rpm for 10 min. Next, cationic photoinitiator, sensitizer and free radical initiator were added and stirred at 1500 rpm for 2 min to complete the premixing and obtain the adhesive solution. The adhesive solution was transferred to a vacuum degassing autoclave and degassed under vacuum at 80℃ for 2 h to obtain the UV-cured epoxy resin adhesive. Performance testing experiment

[0050] (1) The standard GB / T 7124-2008 Determination of tensile shear strength of adhesives (rigid material to rigid material) was selected. The cured sample was installed on a universal testing machine with a tensile speed of 5 mm / min. The maximum load at which the sample failed was recorded and the shear strength was calculated. Five samples were prepared for each sample. The average value was taken after measurement and the initial shear strength was calculated. The cured sample was placed in a high-temperature oven and kept at 150℃ for 7 days. After being taken out, it was cooled in an environment of 23℃ and 50% humidity for 2 hours. The shear strength after heat aging was tested. Five samples were prepared for each sample. The average value was taken after measurement and the heat resistance strength retention rate was calculated. The cured sample was placed in deionized water at 85℃ and soaked for 7 days. After being taken out, the surface moisture was absorbed with filter paper and placed in an environment of 23℃ and 50% humidity for 2 hours. The shear strength after water curing was tested. Five samples were prepared for each sample. The average value was taken after measurement and the water resistance strength retention rate was calculated. The results were recorded in Table 1.

[0051] (2) Select GB / T 24148.9-2014 Plastic Unsaturated Polyester Resin (UP-R) Part 9: Determination of Total Volume Shrinkage as the standard, test the volume shrinkage rate of the sample, prepare three samples for each sample, take the average value after measurement, and record the results in Table 1.

[0052] (3) The standard GB / T 7123.2-2002 Determination of the shelf life of adhesives was selected. The initial viscosity and the viscosity after storage were tested. After 180 days of storage at 25℃, the viscosity increase was ≤100%, and there was no gel or precipitation. It was determined that it could be stored for a long time at room temperature (√). The results are recorded in Table 1.

[0053] (4) Curing depth test: The sample is injected into a transparent polytetrafluoroethylene tube with an inner diameter of 5 mm and a length of 50 mm. One end of the tube is completely shielded from light with black tape, and UV irradiation (365 nm, 100 mW / cm², irradiation time 120 s) is performed from the other end. After curing, the glue stick is pushed out and the actual length of curing from the light-illuminated end to the light-shielded end (i.e., curing depth, unit mm) is measured. The results are repeated 3 times and the average value is taken. The results are recorded in Table 1.

[0054] Table 1. Test results of heat resistance, water resistance, volume shrinkage, storage stability, and curing depth of adhesives. Example 1 92.6 88.6 1.1 √ ≥6 Example 2 94.1 85.8 1.4 √ ≥8 Example 3 91.9 86.5 1.3 √ ≥7 Example 4 94.3 90.9 0.8 √ ≥7 Example 5 94.8 91.5 0.7 √ ≥7 Example 6 95.1 91.9 0.5 √ ≥8 Example 7 93.1 90.0 0.9 √ ≥7 Example 8 92.5 89.5 1.0 √ ≥6 Example 9 88.9 86.7 1.5 √ ≤5 Comparative Example 1 88.1 85.3 1.6 √ ≤3 Comparative Example 2 85.6 85.9 2.0 √ ≤4 As shown in Table 1, the heat resistance retention rate of Examples 1-3 is greater than 91.9%, the water resistance retention rate is greater than 85.8%, the volume shrinkage rate is less than 1.4%, the storage stability is good, and the curing depth is greater than 6 mm. This shows that the adhesive prepared in this application has good heat resistance, water resistance and storage stability, and has low volume shrinkage rate and high curing depth.

[0055] As shown in Table 1, the difference between Examples 4-9 and Example 3 is only that: in Examples 4-6, alicyclic epoxy resins were compounded according to a defined ratio, and the performance of the adhesive was improved through the synergistic effect of the two resins; in Examples 7 and 8, the defined ratio was broken, and the performance improvement effect was reduced; in Example 9, only a single poly[(2-epoxyethylene)-1,2-cyclohexanediol]2-ethyl-2-(hydroxymethyl)-1,3-propanediol ether was used. The pure rigid multifunctional epoxy system had a high crosslinking density, high internal stress of the cured product, high network brittleness, and deteriorated performance.

[0056] As shown in Table 1, the only difference between Comparative Examples 1 and 2 and Example 3 is that: no free radical initiator was added in Comparative Example 1, the deep thermal initiation mechanism failed, the crosslinking network was lacking, the heat and water resistance decreased, and the shrinkage rate increased; no flexible bridging agent was added in Comparative Example 2, the rigidity of the system increased but the toughness decreased, and the performance decreased.

[0057] This specific embodiment is merely an explanation of this application and is not intended to limit it. Based on the above description, those skilled in the art can make various changes and modifications without departing from the technical concept of this application. The technical scope of this application is not limited to the contents of the specification but must be determined according to the scope of the claims.

Claims

1. A UV-curable epoxy resin adhesive, characterized in that: The raw materials for preparation include the following components in parts by weight: 35-45 parts of alicyclic epoxy resin 15-25 parts toughening filler 1-3 parts of fumed silica 10-20 parts of flexible bridging agent 15-25 parts of silicon micro powder 0.8-1.2 parts of cationic photoinitiator 0.8-1.2 parts of free radical initiator Sensitizer 0.8-1.2 parts; The flexible bridging agent includes polyether polyol; The toughening filler includes methyl methacrylate-butadiene-styrene copolymer; The alicyclic epoxy resin further includes poly[(2-epoxyethylene)-1,2-cyclohexanediol]2-ethyl-2-(hydroxymethyl)-1,3-propanediol ether; The mass ratio of the 3',4'-epoxycyclohexylmethyl-3,4-epoxycyclohexane carboxylate to poly[(2-epoxyethylene)-1,2-cyclohexanediol]2-ethyl-2-(hydroxymethyl)-1,3-propanediol ether is 1:(0.2-0.3).

2. The UV-curable epoxy resin adhesive according to claim 1, characterized in that: The cationic photoinitiator includes aryl thioonium salt derivatives.

3. The UV-curable epoxy resin adhesive according to claim 1, characterized in that: The free radical initiator includes cumene peroxide.

4. The UV-curable epoxy resin adhesive according to claim 1, characterized in that: The sensitizer includes 5,7-diiodo-3-butoxy-6-fluorescein.

5. The UV-curable epoxy resin adhesive according to claim 1, characterized in that: The alicyclic epoxy resin includes 3',4'-epoxycyclohexylmethyl-3,4-epoxycyclohexane carboxylate.

6. A method for preparing a UV-curable epoxy resin adhesive as described in any one of claims 1-5, characterized in that: Includes the following steps: After stirring and dispersing alicyclic epoxy resin, toughening filler and flexible bridging agent, fumed silica and silica powder are added, and after stirring, cationic photoinitiator, sensitizer and free radical initiator are added. After stirring to complete the premixing, a glue solution is obtained. The glue solution is degassed under vacuum to obtain UV-curable epoxy resin adhesive.